2010
DOI: 10.1111/j.1467-789x.2009.00645.x
|View full text |Cite
|
Sign up to set email alerts
|

The relation between an adverse psychological and social environment in childhood and the development of adult obesity: a systematic literature review

Abstract: The prevalence of obesity is on a global-wide increase, but still the aetiology of adult obesity is poorly understood. It has been shown that overweight children suffer from adverse psychological events, but less is known about the potential effects of adverse psychological factors among normal weight children for later development of obesity. The purpose of this study was to systematically review current literature on associations between psychological factors in childhood and development of obesity in adulth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 56 publications
7
66
2
2
Order By: Relevance
“…While our study found a higher prevalence of withdrawn/depressed in obese children, like other authors (Erickson, Robinson, Haydel, & Killen, 2000;Esposito et al, 2014;Morrison et al, 2015;Rankin et al, 2016), our findings did not support a higher prevalence of anxiety problems as shown in other studies (Chiang et al, 2013;Goldfield et al, 2010;Esposito et al, 2014). This association might be observed later in life, as some research has found that symptoms of anxiety or depression during childhood and adolescence predict later obesity (Aparicio et al, 2013;Blaine, 2008;Mannan et al, 2016;Robert & Duong, 2016;Rofey et al, 2009;Vámosi et al, 2010). It is also possible that at early ages, the manifestations of internalizing problems are based more on somatic complaints.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…While our study found a higher prevalence of withdrawn/depressed in obese children, like other authors (Erickson, Robinson, Haydel, & Killen, 2000;Esposito et al, 2014;Morrison et al, 2015;Rankin et al, 2016), our findings did not support a higher prevalence of anxiety problems as shown in other studies (Chiang et al, 2013;Goldfield et al, 2010;Esposito et al, 2014). This association might be observed later in life, as some research has found that symptoms of anxiety or depression during childhood and adolescence predict later obesity (Aparicio et al, 2013;Blaine, 2008;Mannan et al, 2016;Robert & Duong, 2016;Rofey et al, 2009;Vámosi et al, 2010). It is also possible that at early ages, the manifestations of internalizing problems are based more on somatic complaints.…”
Section: Discussioncontrasting
confidence: 78%
“…The etiology of obesity can be understood within a biopsychosocial model that involves multiple factors, such as early-life diet, socio-economic situation, dietary habits, sedentary lifestyle, genetic predisposition, physiological conditions and psychological state (Braet, 2005;Brands, Demmelmair & Koletzko, 2014;Robinson et al, 2015;Spruijt-Metz, 2011;Vámosi, Heitmann, & Kyvik, 2010). The association between psychological problems and being overweight/obese appears to emerge early in life and both are significant public health problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review by Vámosi, Heitmann & Kyvik (2010) has highlighted that fact that stress, abuse and emotional trauma during childhood appear to predispose towards adult obesity, not least because of the learned use of eating as a comfort response, which then continues into adulthood; and a similar picture was found in a brief survey by Brooke & Mussap (2013).…”
Section: Theoretical Basis For Hypnosis In Obesity Treatmentmentioning
confidence: 76%
“…6 Childhood physical, psychological, and sexual abuse and parental neglect have been associated with increased risk for obesity in adulthood. [7][8][9][10][11][12][13][14][15][16] Few of these studies have been among racially/ethnically diverse populations or larger cohorts. Moreover, mechanisms linking childhood adversities and adult health outcomes are poorly understood.…”
mentioning
confidence: 99%